2022
DOI: 10.1115/1.4055754
|View full text |Cite
|
Sign up to set email alerts
|

Flame Transfer Functions for Turbulent, Premixed, Ammonia-Hydrogen-Nitrogen-Air Flames

Abstract: Ammonia is a promising hydrogen and energy carrier but also a challenging fuel to use in gas turbines, due to its low flame speed, limited flammability range, and the production of NOx from fuel-bound nitrogen. Previous experimental and theoretical work has demonstrated that partially-dissociated ammonia can match many of the laminar flame properties of methane flames. Among the remaining concerns pertaining to the use of NH3/H2/N2 blends in gas turbines is their thermoacoustic behavior. This paper presents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In recent years, most studies on thermoacoustic instability have focused on premixed flames of gaseous fuels such as methane and ammonia, while there has been less research on non-premixed flames [14,[33][34][35][36][37], such as those found in gas turbine combustors. However, in recent years, there has been a growing interest in investigating the oscillation characteristics of non-premixed flames.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, most studies on thermoacoustic instability have focused on premixed flames of gaseous fuels such as methane and ammonia, while there has been less research on non-premixed flames [14,[33][34][35][36][37], such as those found in gas turbine combustors. However, in recent years, there has been a growing interest in investigating the oscillation characteristics of non-premixed flames.…”
Section: Introductionmentioning
confidence: 99%